MENGGALI POTENSI DESA UNTUK MEWUJUDKAN DESTINASI WISATA RELIGI - N.M. Witariadi; T.B. Kusmiyarti; I.M. Adhika; I.N. Sujana (Buletin Udayana Mengabdi, 2023)
The Sangketan Village Area Partnership Program, Penebel District, Tabanan Regency aims to create a religious tourism village through: (1) Structuring the Tamba Waras Temple with the taru premana arboretum and upakara plants; (2) Developing freshwater fish by keeping catfish as a tourist attraction and increase income; (3) Development of organic agriculture; and (4) Development and arrangement of BUMDes as a village-owned business facility by helping to process coffee into other products and helping to distribute community products. The methods applied to achieve these goals are through education, training, science and technology simulations, mentoring, and applied design and appropriate technology. The approaches used include: (1) transfer of appropriate technology to the community (2) Development of entrepreneurial insight, and (3) use of IT (e-commers to establish tourism attraction partnerships). Activities carried out include: (1) Socialization, coordination and setting targets; (2) the arrangement of the Tamba Waras Temple with the taru premana arboretum and upakara plants; (2) Development of freshwater fish (catfish) as a tourist attraction and increase the income of temple managers; (3) Development of organic agriculture; (4) Improvement and assistance of BUMDes as village-owned enterprises and production sites as well as distribution of community products; (5) Monitoring, supervision, and evaluation; and (6) Journal reporting and publication. Keywords: aboretum taru premana, Bumdes, catfish, organic farming and religious tourism.